Temptations of Power - Jackson, R. author. aut Link
XIV, 228 p.
Keywords: Temptations of Power examines the new security dilemma which confronted George W. Bush when terrorists proved on 9/11 that they could seriously wound a great military powers on home ground. The authors argue that the response was influenced by neo-conservative exaggeration of the efficacy of military power and belief in the US ability.